2015
DOI: 10.1186/s12879-015-1235-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-typhoidal Salmonella serotypes, antimicrobial resistance and co-infection with parasites among patients with diarrhea and other gastrointestinal complaints in Addis Ababa, Ethiopia

Abstract: BackgroundNon-typhoidal Salmonella (NTS) is an important public health problem worldwide. Consumption of animal-derived food products and direct and/or indirect contact with animals are the major routes of acquiring infection with NTS. Published information, particularly on the serotype distribution of NTS among human patients with gastroenteritis and associated risk factors, is scarce in Ethiopia. This study investigated the prevalence, risk factors, serotype distribution and antimicrobial susceptibility of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
61
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 38 publications
17
61
10
1
Order By: Relevance
“…An alarming increase in the antibiotic resistance by NTS was reported elsewhere (11,12). In our study, 54.3% of our isolates were found to be resistant to nalidixic acid, which is lower than that reported from India (77%) (22), Southwest China (66.7%) (27), and higher than that reported from Congo (4.3%) (33), Iraq (45.5%) (23), Ethiopia (23.9%) (34), and Iran (31.5%) (17). Among the NTS isolated from stool samples, Nalidixic acid was predominant among our NTS, (64.8%) which was very much higher than that reported from Kenya (6%) (16).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…An alarming increase in the antibiotic resistance by NTS was reported elsewhere (11,12). In our study, 54.3% of our isolates were found to be resistant to nalidixic acid, which is lower than that reported from India (77%) (22), Southwest China (66.7%) (27), and higher than that reported from Congo (4.3%) (33), Iraq (45.5%) (23), Ethiopia (23.9%) (34), and Iran (31.5%) (17). Among the NTS isolated from stool samples, Nalidixic acid was predominant among our NTS, (64.8%) which was very much higher than that reported from Kenya (6%) (16).…”
Section: Discussioncontrasting
confidence: 59%
“…Distribution of Non-Typhoidal Salmonella Species a We found that antibiotic resistance by NTS towards nalidixic acid was significantly higher than other tested antibiotics (ANOVA, F = 0.23; P < 0.05).Of the 38 iNTS isolates, the majority of the isolates were resistant to ciprofloxacin (19, 50%) followed by cefotaxime (17, 44.7%), gentamicin(16, 42.1%), nalidixic acid (15, 39.5%), amoxicillin(13,34.2%), ampicillin(12,31.6%), cotrimoxazole (10, 26.3%), amikacin (9, 23.7%) and chloramphenicol(8, 21.1%) …”
mentioning
confidence: 93%
“…A strain of serotype V: rough-O;-:- that was susceptible to nalidixic acid but intermediately resistant to ciprofloxacin had single substitution of Ser463-Ala on gyr B gene. Over half of the quinolone resistant isolates in the current study 17 (58.6%) were also resistant to at least one of the beta-lactam antimicrobials (Table 5) and all S. Kentucky isolates resistant to nalidixic acid and ciprofloxacin were also shown to be MDR to several antimicrobials in our previous works [27, 28]. No mutation was detected in par E gene in any of the isolates examined in the current study.…”
Section: Resultssupporting
confidence: 47%
“…The inhibition zone sizes were interpreted based on CLSI guidelines. Escherichia coli ATCC 25922 was used as quality control strain (Eguale et al 2015).…”
Section: Methodsmentioning
confidence: 99%